Yes but No: Media Frames for Denying Nurses' Strikes during COVID-19 Recovery - Torssonen, Sami (Helsinki University Press, 2025)
The COVID-19 pandemic saw nurses strike throughout the world in the face of fierce opposition from employers and states. Publicly justifying the opposition to nurses' demands was, however, unprecedentedly difficult due to the profession's pandemic-induced popularity. This article takes a Marxist ideology-theoretical approach to media discourse opposing nurse strikes in Germany, Finland and the UK in 2022 and early 2023 to uncover how newspaper texts faced the situation, with a special focus on texts that attacked nurses. The results show that misogynous gender and unprofessionalism frames, recognised in previous nurse strike literature, had been abandoned nearly completely. Instead, ideological media frames attacked nurses with reference to ideological values drawn from domains such as economics and law while undermining working-class solidarity. Furthermore, nurse strike frames in this period frequently exhibited what is here dubbed a 'yes but no' frame that anticipated audience sympathy for nurses by praising them while invalidating their concrete demands. Germany stood out, however, for its seemingly muted and regional ideological backlash, corresponding with German nurses' modest demands and the country's relatively decentralised healthcare system.